2021
DOI: 10.1088/1361-6501/ac0b6d
|View full text |Cite
|
Sign up to set email alerts
|

A combined algorithm for denoising GNSS-RTK positioning solutions with application to displacement monitoring of a super-high-rise building

Abstract: Given that global navigation satellite system (GNSS)-based real-time kinematic (GNSS-RTK) monitoring accuracy is easily interfered with by residual errors, a combined algorithm is proposed for signal denoising with application to the GNSS-RTK positioning solutions of a super-high-rise building; namely, the Tianjin Radio and Television Tower in China. The proposed denoising algorithm is a combination of the Butterworth high-pass filter and complete ensemble empirical mode decomposition with adaptive noise (CEEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Additionally, the proposed method is useful and potentially inspiring for related research fields. Typically, strong multipath GNSS measurement sequences using the DD technology are not detrimental to deformation monitoring in realtime [44]. If a multipath can be predicted in real time, the accuracy of deformation monitoring can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the proposed method is useful and potentially inspiring for related research fields. Typically, strong multipath GNSS measurement sequences using the DD technology are not detrimental to deformation monitoring in realtime [44]. If a multipath can be predicted in real time, the accuracy of deformation monitoring can be improved.…”
Section: Discussionmentioning
confidence: 99%
“…How to find an effective algorithm to better evaluate the modal parameters of the bridge from the noisy signal responses has consistently attracted the interest of researchers. Some time-frequency domain analysis methods are employed to decompose signal responses into several intrinsic mode functions (IMFs) and thus separate noise components, like empirical wavelet transform (EWT) [14,15], empirical mode decomposition (EMD) [16][17][18], ensemble empirical mode decomposition (EEMD) [19][20][21], complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN) [22][23][24], variational mode decomposition (VMD) [25][26][27][28]. Tao et al [29] proposed the EWT method to reduce the noise in the GNSS coordinate system and demonstrated that the signal after EWT denoising was close to the original signal.…”
Section: Introductionmentioning
confidence: 99%